2021
DOI: 10.1021/acs.jafc.1c01970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polyphenol Interactions with Titanium Dioxide Nanoparticles on Their Bioavailability and Antioxidant Activity

Abstract: Titanium dioxide is widely utilized as a pigment in the food industry to enhance the whiteness or brightness of foods and beverages. The powdered forms of titanium dioxide used as food ingredients contain a substantial fraction of nanoparticles (d < 100 nm), which may have adverse effects on human health. This is a model study that investigated the molecular interactions between TiO 2 nanoparticles and selected polyphenols, as well as their influence on the in vitro bioavailability and antioxidant activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Chitosan has good biocompatibility, biodegradability, safety, and non-toxic properties. The wealthy functional groups on its molecular surface can form hydrogen bonds with glycoproteins in mucus and adsorb to the mucosal surface, which can prolong the retention time of the encapsulated drugs or active substances in the human intestine, release continuously, and improve the bioavailability of the encapsulated substances ( Li et al, 2021b ). In a comprehensive view, the enhancement of antioxidant activity expression by tea polyphenol nanoparticles can be attributed to two aspects: one is that the nanoparticles form a rough hydrophobic core or particular network structure, which limits the migration of tea polyphenols, realizes the slow release of tea polyphenols, extends the antioxidant time, and thus improves the antioxidant activity; The other is to form a polymer wall to encapsulate tea polyphenols inside, reducing the oxidation and degradation rate of tea polyphenols, thus achieving the effect of protecting tea polyphenols ( Liu et al, 2022 ).…”
Section: Oil Oxidation Mechanism and Inhibition Strategymentioning
confidence: 99%
“…Chitosan has good biocompatibility, biodegradability, safety, and non-toxic properties. The wealthy functional groups on its molecular surface can form hydrogen bonds with glycoproteins in mucus and adsorb to the mucosal surface, which can prolong the retention time of the encapsulated drugs or active substances in the human intestine, release continuously, and improve the bioavailability of the encapsulated substances ( Li et al, 2021b ). In a comprehensive view, the enhancement of antioxidant activity expression by tea polyphenol nanoparticles can be attributed to two aspects: one is that the nanoparticles form a rough hydrophobic core or particular network structure, which limits the migration of tea polyphenols, realizes the slow release of tea polyphenols, extends the antioxidant time, and thus improves the antioxidant activity; The other is to form a polymer wall to encapsulate tea polyphenols inside, reducing the oxidation and degradation rate of tea polyphenols, thus achieving the effect of protecting tea polyphenols ( Liu et al, 2022 ).…”
Section: Oil Oxidation Mechanism and Inhibition Strategymentioning
confidence: 99%
“…Compared the DPPH˙ scavenging ability with other antioxidants or nanoparticles (Table S2†), Ti 3 C 2 can remove DPPH˙ in a smaller dose and shorter time, which indicates that Ti 3 C 2 has strong free radical scavenging ability and fast response. 48–51…”
Section: Resultsmentioning
confidence: 99%
“…Compared the DPPHc scavenging ability with other antioxidants or nanoparticles (Table S2 †), Ti 3 C 2 can remove DPPHc in a smaller dose and shorter time, which indicates that Ti 3 C 2 has strong free radical scavenging ability and fast response. [48][49][50][51] Considering ROS play the critical role in regulation of oxidative stress balance, three representative ROS in biological conditions, H 2 O 2 , cOH and O À$ 2 , were selected to investigate systematically the powerful ROS scavenging capabilities of Ti 3 C 2 . The ability of Ti 3 C 2 to reduce H 2 O 2 is evaluated by using HRP-H 2 O 2 -TMB system, which is a classic enzymatic reaction.…”
Section: Antioxidant Activity Of Ti 3 C 2 Nss By Scavenging Free Radi...mentioning
confidence: 99%
“…Previously, we showed that various kinds of plant proteins, including glutenin and zein, can interact with TiO 2 nanoparticles and form protein coronas . Other studies have shown that other kinds of food ingredients can also bind to the surfaces of TiO 2 nanoparticles, including animal proteins (casein), tea polyphenols, and polymethoxyflavones. This not only changed the physicochemical properties and behavior of the nanoparticles but also reduced the bioavailability and bioactivity of the nutrients. , …”
Section: Introductionmentioning
confidence: 99%